The Cape Town Declaration on access to cardiac surgery in the developing world - Zilla, Peter; Bolman, R.Molton; Yacoub, Magdi H.; Beyersdorf, Friedhelm; Sliwa, Karen; Zuhlke, Liesl; Higgins, Robert S.; Mayosi, Bongani; Carpentier, Alain; Williams, David (SA Heart Journal, 2018)
The mission of this declaration is to urge all relevant entities within the international cardiac surgery, industry, and government sectors to commit to develop and implement an effective strategy to address the scourge of rheumatic heart disease in the developing world through increased access to lifesaving cardiac surgery.